Hierarchical Medical: What are the Factors Driving ESKD Patients to Choose Community Hemodialysis Centers in China? A Labelled Discrete Choice Experiment - Xiong J; Zhang H; Ma H (Patient Preference and Adherence)
Juyang Xiong, Hangjing Zhang, Huimin Ma School of Medicine and Health Management, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, People’s Republic of ChinaCorrespondence: Juyang Xiong, School of Medicine and Health Management, Tongji Medical College, Huazhong University of Science and Technology, 13 hang Kong Road, Qiaokou District, Wuhan City, Hubei Province, People’s Republic of China, Email xiongjuyang@hust.edu.cnPurpose: In China, secondary and tertiary hospital-based dialysis facilities had been the most prominent provider of hemodialysis treatment. Developing community hemodialysis centers was the key to constructing hierarchical hemodialysis system. Thus, the aim of this study was to explore end-stage kidney disease (ESKD) patients’ preferences for hemodialysis services and attract patients with stable condition to choose community hemodialysis services.Patients and Methods: The study used a labelled discrete choice experiment with ESKD patients in Wuhan, Hubei Province in China. Patients were asked to make a choice between hospital-based hemodialysis facilities and community hemodialysis centers with different attribute levels. Mixed logit model was used to measure their preferences and heterogeneity for hemodialysis services. The marginal utility was measured to predict the change of patients’ choice probability of community hemodialysis centers.Results: A total of 420 ESKD patients consented to complete the questionnaires and 408 were included in the analysis after excluding responses that did not pass the consistency test. All attributes were significantly influencing respondents’ choice of hemodialysis service. Patients were more inclined to hemodialysis services with smooth and effective referral, regular doctors, 20 minutes of travel time, and home-based offline follow-up. Gender, age, income, hemodialysis year, and hemodialysis times weekly were found to influence the preferences. When the community hemodialysis service attributes gradually meet the patients’ preferences, as many as 58.39% of patients will choose community hemodialysis centers.Conclusion: A better understanding of ESKD patients’ preferences for hemodialysis service is a crucial step for the future policy implementations. Although patients tended to choose hospital-based hemodialysis facilities, patients’ preferences for hemodialysis institutions would reverse with the change of service attribute. Establishing a smooth and effective referral is the most important attribute to improve patients’ acceptance of community hemodialysis centers. Strengthening the integration of service can facilitate hierarchical hemodialysis service system.Keywords: discrete choice experiment, hemodialysis, end-stage renal disease, community hemodialysis centers